M39 Screening For Tuberculomas In Patients With Miliary Tuberculosis – What Modality Of Imaging Should We Be Using?. (10th November 2014) - Ghani, R; Durkan, H; John, L; Davidson, R; Buckley, J
Abstract : Introduction and objectives: NICE guidance advises neuroradiology to investigate CNS signs in patients with miliary tuberculosis (TB). The aims of our study were to describe our population of patients with tuberculomas in the presence of miliary disease and identify any clues to the best radiological modality. Methods: The radiology and clinical history was retrospectively reviewed for all patients treated for miliary tuberculosis at one centre between 01/01/2009 and 31/12/2013. Results: 53/1650 (3.2%) of patients during this period were diagnosed with miliary (disseminated) tuberculosis. 27/53 (50.9%) underwent further neuroimaging. 10/53 (18.9%) miliary TB patients had evidence of tuberculomas on neuroimaging (M:F 6:4, age range 22:81). 2/10 had evidence of tuberculomas on both CT (2/2 with contrast) and MRI, 5/10 had a negative CT (2/5 with contrast) but an MRI result which revealed tuberculomas. 3 patients did not have a CT scan (MRI only). All 10 patients were HIV negative and had fully sensitive TB, 9/10 had neurological signs which warranted the subsequent neuroimaging. Conclusion: Tuberculomas are seen in a fifth of patients with miliary tuberculosis. Based on our findings, guidelines should be adapted to suggest that both use of contrast and MRI should be utilised preferentially.